Investigation of aliovalent transition metal doped La0.7Ca0.3Cr0.8X0.2O3−δ (X=Ti, Mn, Fe, Co, and Ni) as electrode materials for symmetric solid oxide fuel cells. Issue 9 (November 2015) - Rath, Manasa K.; Lee, Ki-Tae
Abstract: The crystal phase, chemical stability, thermal expansion behavior, oxygen non-stoichiometry, electrical conductivity, and electro-catalytic activity of La0.7 Ca0.3 Cr0.8 X0.2 O3− δ (X=Ti, Mn, Fe, Co, and Ni) electrode materials have been investigated. All the compositions are chemically stable with a single-phase perovskite structure in both reducing and oxidizing atmospheres at high temperature. The linear thermal expansion coefficients of La0.7 Ca0.3 Cr0.8 X0.2 O3− δ are approximately 10×10 −6 K −1 . The total electrical conductivity of La0.7 Ca0.3 Cr0.8 X0.2 O3− δ increases in the order of X=Ti<Ni<Fe<Co<Mn, which is correlated to the porosity, valence orbital ionization potential, and oxygen non-stoichiometry upon the reduction process. The overall reaction process of the hydrogen oxidation for the La0.7 Ca0.3 Cr0.8 X0.2 O3− δ anodes is limited by the charge transfer process that requires higher activation energy. In a similar trend observed in electrical conductivity, La0.7 Ca0.3 Cr0.8 Mn0.2 O3− δ exhibits the lowest polarization resistance value of 0.12 Ω cm 2 at 800 °C. Finally, the symmetric single cell with La0.7 Ca0.3 Cr0.8 Mn0.2 O3− δ as both the cathode and anode shows a maximum powder density of 220 mW cm −2 at 800 °C.